Comparing glutamatergic neuron population in the mediodorsal thalamic nucleus of genetic absence epilepsy rats from strasbourg (GAERS) and normal control Wistar rats - ONAT, FİLİZ; KİRAZLI, ÖZLEM (ELSEVIER SCIENCE BV, 2016)
An imbalance between GABAergic inhibition and glutamatergic excitation is suspected to play a role in the genesis of epileptic processes. In the present study we quantified the number of glutamate+ve neurons in the mediodorsal thalamic nucleus (MD) of genetic absence epilepsy rats from Strasbourg (GAERS) and compared these with values for normal Wistar rats. The MD thalamic nucleus was removed from each animal and the glutamatergic neurons were labelled using light-microscopy glutamate immunohistochemistry. The disector method was used to quantify the glutamate+ve neurons in the MD thalamic nucleus of GAERS and Wistar rats. The data were statistically analyzed. In the Wistar animals glutamate+ve neurons formed 89% and in GAERS 92.3% of the total neurons in 1000 mu m(3) of MD thalamic nucleus. In GAERS glutamate+ve neurons showed statistically significant increase in the MD thalamic nucleus compared to Wistar animals. In Wistar animals the glutamate-ve neurons formed 11% and in GAERS 7.7% of the total neurons in 1000 mu m(3) of MD thalamic. No significant difference was observed in glutamate ye neurons between the two strains. The average diameter of glutamate-ve neurons showed no significance, while glutamate-ve neurons were significant between the two strains. The results of the present study, on genetic absence epilepsy model, GAERS, confirms the role of MD thalamic nucleus in chemically induced absence epilepsy. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Glutamate; Mediodorsal thalamic nucleus; Absence epilepsy; Quantification immunohistochemistry; GENERALIZED PENICILLIN EPILEPSY; MAL-LIKE SEIZURES; WAVE DISCHARGES; NONCONVULSIVE EPILEPSY; CORTEX; MODEL; SPIKE; MECHANISMS; SCHIZOPHRENIA; POSTMORTEM